PERKUATAN GESER KOLOM BETON BERTULANGBERPENAMPANG PERSEGI DENGAN KAWAT KASA METODEMORTAR JACKETING BERPENAMPANG BULAT - dan Suprapto Siswosukarto (2), Dian Eksana W (1), Andreas Triwiyono (2) (INERSIA lnformasi dan Ekspose Hasil Riset Teknik Sipil dan Arsitektur, 2012)
ABSTRACTColum reinforcement is essential in a structure. When a column is weak, itwill cause total failure to the structure. This study examined the behavior of columnreinforced with mortar jacketing method and wire netting. The objective of this studywas to identify the contribution of the reinforcement to the shear strength and columnductility. Four column specimens were made. They consisted of one original column(as comparison) in square shape of 150 x 150 mm, and 700 mm height andfoundation plate in 1200 x 700 mm with 250 mm thickness and three specimens insame dimensions and strengthened by mortar jacketing to become column withround section in 220 mm diameter and 730 mm height. Longitudinal reinforcementand wire netting in 1.7 mm diameter and consisted of small squares of 25 mm x 25mm with 1 layer strengthening (KP-1). Two layers (KP-2), and 3 layers (KP-3) wereused as the mortar jacketing. Sika Grout 215 New was used as the filler. Loadingtype used was constant axial and cyclic lateral to simulate earthquake by using thedisplacement control method. The results showed that in KP-1, KP-2 and KP-3reinforced column, their lateral load capacities increased by 90.263%, 101.985%,124.196%, respectively, than the average original column (KA-1). Addition of wirenetting for KP-1, KP-2, and KP-3 showed general increase of displacement at amaximum lateral load in compare to the original column (KA-1). Drift ratio atmaximum load at KA-1 was 2.07%. As for KP-1dan KP-3, the maximum loadswere 2.52 % and 2.924%, respectively. However, the drift ratio of KP-2 was1.192%, or smaller than 1.50%. The stiffness values obtained from the testsfor KA-1, KP-1, KP-2 and KP-3 were 3.92 KN/mm, 9.04 KN/mm, 9.01kN/mm,and 8.14kN/mm, respectively. Ductility factor (Î¼) of KA-1, KP-1, KP-2, and KP-3were 5.451, 6.273, 3.938, and 6.667, respectively. Thus, more netting wire showedincreasing ductility, except for KP-2 which had the smallest ductility in compare toother specimens. Based on the test results and the regulation of ACI 374.1-05.200,the reinforced column could be used for structures with maximum R (responsemodification factor) of 6.Keywords : Shear collapse, Mortar jacketing, netting wire, cyclic load